2016
DOI: 10.1038/cdd.2016.133
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tumor apoptosis through a circular RNA enhancing Foxo3 activity

Abstract: Circular RNAs are a class of non-coding RNAs that are receiving extensive attention. Despite reports showing circular RNAs acting as microRNA sponges, the biological functions of circular RNAs remain largely unknown. We show that in patient tumor samples and in a panel of cancer cells, circ-Foxo3 was minimally expressed. Interestingly, during cancer cell apoptosis, the expression of circ-Foxo3 was found to be significantly increased. We found that silencing endogenous circ-Foxo3 enhanced cell viability, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
519
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(527 citation statements)
references
References 29 publications
8
519
0
Order By: Relevance
“…Recent studies suggest that circRNAs play vital roles in tumour procession, including cell apoptosis, angiogenesis and cell cycle progression. 12,13 And circRNAs could be promising prognostic biomarkers and therapeutic targets in tumour treatment. 14,15 But the expression and function of circRNAs in glioma are still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that circRNAs play vital roles in tumour procession, including cell apoptosis, angiogenesis and cell cycle progression. 12,13 And circRNAs could be promising prognostic biomarkers and therapeutic targets in tumour treatment. 14,15 But the expression and function of circRNAs in glioma are still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is considered to be the major mechanism of programmed cell death, and the maintenance of normal physiology and cellular homeostasis occurs through different mechanisms . Apoptosis regulates diverse cellular processes, including cell proliferation, the cell cycle and survival, and the results of previous studies have suggested that the inhibition of PI3K/AKT signalling induces apoptosis …”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is considered to be the major mechanism of programmed cell death, and the maintenance of normal physiology and cellular homeostasis occurs through different mechanisms. [11][12][13] Apoptosis regulates diverse cellular processes, including cell proliferation, the cell cycle and survival, 14,15 and the results of previous studies have suggested that the inhibition of PI3K/AKT signalling induces apoptosis. 16,17 In this study, we aimed to determine the expression profile and elucidate the pathological functions of PLAC8 during BC progression, and our results revealed a relationship between endogenous PLAC8 expression and PI3K/AKT pathway activity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this group found that circFoxo3 was downregulated in patient tumor samples and in a group of cancer cells, whereas it was upregulated in the cancer cells when the cells were induced to undergo apoptosis. 2 The authors showed that silencing endogenous circFoxo3 produced an opposite effect, while ectopic circ-Foxo3 induced cell apoptosis and inhibit progression of tumor xenografts. Interestingly, ectopic circ-Foxo3 played roles in increasing Foxo3 protein levels.…”
mentioning
confidence: 99%